2015
DOI: 10.1002/chem.201501024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ba[CoSO]: Magnetic Complexity in the Presence of Chalcogen Ordering

Abstract: Barium thio-oxocobaltate(II), Ba[CoS2/2 O2/2 ], was synthesized by the reaction of equimolar amounts of BaO, Co, and S in closed silica ampoules. The title compound (Cmcm, a=3.98808(3), b=12.75518(9), c=6.10697(4) Å) is isostructural to Ba[ZnSO]. The use of soft X-ray absorption spectroscopy confirmed that cobalt is in the oxidation state +2 and tetrahedrally coordinated. Its coordination consists of two sulfur and two oxygen atoms in an ordered fashion. High-temperature magnetic susceptibility data indicate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 35 publications
11
41
0
Order By: Relevance
“…The GGA+U calculations have also shown that with a reasonable U value, the material is in an AFM ordered state with a magnetic moment about 2.7µ B per Co atom [9]. In Fig.4, we confirm these results and plot the band structures without U and with U=3eV.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The GGA+U calculations have also shown that with a reasonable U value, the material is in an AFM ordered state with a magnetic moment about 2.7µ B per Co atom [9]. In Fig.4, we confirm these results and plot the band structures without U and with U=3eV.…”
supporting
confidence: 79%
“…The bulk BaCoSO has been measured experimentally to be an AFM insulator [8,9]. The GGA+U calculations have also shown that with a reasonable U value, the material is in an AFM ordered state with a magnetic moment about 2.7µ B per Co atom [9].…”
mentioning
confidence: 92%
“…For tetrahedra, 3+1 and 2+2 coordinations are possible (Figure 3), of which a distorted type of the former is seen for Fe 2+ (HS, d 6 ) in AEFe 2 Ch 2 O (AE = Ba 2+ , Sr 2+ , Ch = S 2´, Se 2´) [38][39][40][41] and in CaFeSO [43]. The latter 2+2 coordination is found for TM 2+ in BaTMSO (TM = Zn 2+ [8], Co 2+ HS, d 7 [46]) and Fe 2+ (HS, d 6 ) in CaFeSeO [47]. Cis and trans 2+2 distorted square planar coordinations of two electronically noble-gas-like anions have not been reported in bulk material to date, but should be possible.…”
Section: Coordination Configurations and Crystal Field Effectsmentioning
confidence: 99%
“…The S´O ordering in BaCoSO [46] constitutes a new type of parameter causing magnetic anisotropy (Figure 7). The extraordinary bonding situation results in two different super-exchange paths, Co´S´Co and Co´O´Co, that run parallel to two orthogonal crystallographic directions, a and c, respectively (Figure 7).…”
Section: Magnetic Anisotropymentioning
confidence: 99%
“…. It has been reported that the CaCoSO is isostructural with CaZnSO, BaCoSO and CaFeSO3637383940. Since the newly synthesized CaCoSO crystallizes in non-centro-symmetry, this results in the loss of inversion symmetry, which in turn gives a considerable SHG.…”
mentioning
confidence: 98%